A Cybersecurity Model for a Roblox-based Metaverse Architecture Framework (Global Journal of Computer Science and Technology, 2023)
The adoption of virtual reality VR and augmented reality AR headsets in futuristic and science fiction has made it possible for the Metaverse to exist as a single universal immersive virtual universe By extending technology outside of our physical reality the Metaverse alters the human experience The four categories we use to categorize metaverse definitions are environment interface interaction and social value Currently it is unclear what the metaverse s structure and elements are A cybersecurity framework for these devices is necessary as the world grows more interconnected and immersive technologies are increasingly widely used in business government and consumer markets Used was a literature review
Keywords: metaverse; augmented reality; virtual reality; internationalization; e-learning; cybersecurity